587 PATIENT-REPORTED SYMPTOMS FOR ESOPHAGEAL CANCER PATIENTS UNDERGOING CURATIVE INTENT TREATMENT. (17th September 2021) - Gupta, Vaibhav; Allen-Ayodabo, Catherine; Davis, Laura; Zhao, Haoyu; Hallet, Julie; Mahar, Alyson; Ringash, Jolie; Kidane, Biniam; Darling, Gail; Coburn, Natalie
Abstract: : Esophageal cancer (EC) patients experience considerable symptom burden from treatment. This study utilized population-level patient-reported Edmonton Symptom Assessment System (ESAS) scores collected as part of standard clinical care to describe symptom trajectories and characteristics associated with severe symptoms for patients undergoing curative intent EC treatment. Methods: EC patients treated with curative intent at regional cancer centers and affiliates between 2009–2016 and assessed for symptoms in the 12 months following diagnosis were included. ESAS measures nine common patient-reported cancer symptoms. The outcome was reporting of severe (≥7/10) symptom scores. Multivariable analyses were used to identify characteristics associated with severe symptom scores. Results: 1, 751 patients reported a median of 7 (IQR 4–12) ESAS assessments in the year following diagnosis, for a total of 14, 953 unique ESAS assessments included in the analysis. The most frequently reported severe symptoms were lack of appetite (n = 918, 52%), tiredness (n = 787, 45%) and poor wellbeing (713, 40.7%). The highest symptom burden is within the first five months following diagnosis, with moderate improvement in symptom burden in the second half of the first year. Characteristics associated with severe scores for all symptoms included female sex, high comorbidity, lower socioeconomic status, urban residence, and symptom assessment temporally close to diagnosis. Conclusion: This study demonstrates a high symptom burden for EC patients undergoing curative intent therapy. Targeted treatment of common severe symptoms, and increased support for patients at risk for severe symptoms, may enhance patient quality of life.